2023
DOI: 10.1139/cjss-2022-0129
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of native wetland species in shallow capped centrifuged tailings and co-mixed tailings: a meso-scale greenhouse study

Abstract: This three-year meso-scale greenhouse study used 55-gallon columns to evaluate the survival and growth of boreal wetland communities planted on centrifuge (CF) tailings and co-mixed (CM) tailings capped with different reclamation cover soil capping designs. The CF tailings were capped with a shallow layer (10 and 30 cm) of peat reclamation material (PRM) and the CM tailings were capped with a shallow layer (5 cm) of PRM above (15 or 35 cm) of reclamation subsoil (till). After three years, plant survival and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…This delayed response is likely a result of plant roots extending from their soil plugs into the TT, or from the PMM into the TT, increasing the root area exposed to TT at different times, depending on the treatment. Similar trends have been observed in other 3 year column studies (Degenhardt et al 2023) and highlight the importance of long-term monitoring of greenhouse or field studies to better understand the plant response to different tailings capping designs.…”
Section: Plant Response Over Timesupporting
confidence: 85%
See 4 more Smart Citations
“…This delayed response is likely a result of plant roots extending from their soil plugs into the TT, or from the PMM into the TT, increasing the root area exposed to TT at different times, depending on the treatment. Similar trends have been observed in other 3 year column studies (Degenhardt et al 2023) and highlight the importance of long-term monitoring of greenhouse or field studies to better understand the plant response to different tailings capping designs.…”
Section: Plant Response Over Timesupporting
confidence: 85%
“…Similar greenhouse column studies also found that thin reclamation caps of peat reclamation material significantly improved plant growth on CF tailings (Degenhardt et al 2023) and reclamation caps of peat reclamation material and till significantly improved growth on CM tailings (Degenhardt et al 2023). Luna Wolter and Naeth (2014) found that soil caps (either PRM or LFH [upland surface soil coversoil]) improved the growth of native grasses on mature fine tailings (MFT), Lalonde et al (2020) found that soil caps (PRM, FFM [upland surface soil coversoil] or both) improved the growth of Populus tremuloides and Salix bebbiana on CF tailings, and Zhang et al (2020) found that the addition of top soil and PMM to non-segregated tailings significantly improved the growth of native woody species (Zhang et al 2020).…”
Section: Plant Response To Pmm Cap and Cap Thicknesssupporting
confidence: 52%
See 3 more Smart Citations